High pressure effects on hydrate Cu-BTC investigated by vibrational spectroscopy and synchrotron X-ray diffraction. Issue 87 (7th December 2017) - Dong, Zhaohui; Mi, Zhongying; Shi, Weiguang; Jiang, Hui; Zheng, Yi; Yang, Ke
Abstract : The high pressure behaviors of hydrate Cu-BTC metal–organic framework (MOF) in terms of phase stability, compressibility and reversibility were investigated in situ by synchrotron X-ray powder diffraction as well as vibrational spectroscopy. Abstract : The high pressure behaviors of hydrate Cu-BTC metal–organic framework (MOF) in terms of phase stability, compressibility and reversibility were investigated in situ by synchrotron X-ray powder diffraction as well as vibrational spectroscopy. Two phase transitions, caused by the interaction of water and the sample framework, were revealed by the vibrational spectroscopies. Compressibility of the hydrate Cu-BTC also displays soft and hard regimes, which is the same scenario as non-hydrate Cu-BTC with a pressure transmitting medium. It is further confirmed that the residual water molecules in hydrate Cu-BTC can serve as a pressure transmitting medium with small molecule size under high pressure. Our results not only prove the high stability of Cu-BTC but also provide spectroscopic evidence for the interactions taking place between the guest molecules and the sample framework. Such findings could provide further guidelines for improving Cu-BTC's absorption and storage abilities.